Community Care of Geriatric Population in Pandemic & Beyond - Singh , Rajendra (South Asian Journal of Social Sciences and Humanities, 2020)
The rapid growth in population is invisible. We are growing and aging just not as an individuals or communities but as a world. In 2006, almost 500 million people worldwide were 65 plus years old. By 2030, that total is projected to be 1 billion i.e.1 in every 8th of the earth’s inhabitants. Significantly, the most rapid increases in the 65 plus older population are occurring in developing countries. In the next 10 to 15 years, the loss of health and life in every region of the world will be greater from non-communicable/chronic or lifestyle diseases such as heart disease, cancer, diabetes etc. Elderly age group is one of the most vulnerable categories for infectious diseases as for example COVID-19 infection. In this infection the high risk of death is due to decreased immunity, decline in body reserves and multiple co-morbid conditions with multiple treatment regimens. COVID-19 is an acute respiratory illness caused by novel corona virus (SARS-CoV-2). It causes higher mortality among elderly persons, particularly in persons with underlying medical conditions, such as cardiovascular disease, chronic respiratory disease, diabetes, cancer etc. Due care can be provided to this vulnerable group, if the community is aware about means & ways to protect them.